2021
DOI: 10.3390/jcdd8070073
|View full text |Cite
|
Sign up to set email alerts
|

Head to Head Comparison between Different 3-Dimensional Echocardiographic Rendering Tools in the Imaging of Percutaneous Edge-to-Edge Mitral Valve Repair

Abstract: MitraClip (MC) is the most common percutaneous treatment for severe mitral regurgitation (MR). An accurate two-dimensional and three-dimensional echocardiographic (3DTEE) imaging is mandatory for the optimal procedural result. Recently transillumination 3DTEE rendering (3DTr) has been introduced integrating a virtual light source into the dataset and with the addition of glass effect (3DGl) allows to adjust tissue transparency improving depth perception and anatomical structure delineation in comparison with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Thus, the display of color blood flow is more comprehensive and clearer. In a past study, Tamborini et al used TrueVue Glass in patients undergoing mitral valve repair and clearly observed the advantages of this method vs. conventional RT3D-TEE imaging in depicting the preoperative regurgitant orifice boundary and identifying the residual shunt after surgery, confirming the value of this technology in interventional procedures for various cardiac diseases (Tamborini et al, 2021). In our study, this advanced 3D cardiac ultrasound technology was systematically applied to the preoperative and postoperative real-time imaging evaluation of LAAO in patients with various forms of LAA, to observe whether the morphology and position of the occluder are normal and to qualify, locate, and quantify any residual leakages around the occluder, providing a basis for individualized treatment planning after surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the display of color blood flow is more comprehensive and clearer. In a past study, Tamborini et al used TrueVue Glass in patients undergoing mitral valve repair and clearly observed the advantages of this method vs. conventional RT3D-TEE imaging in depicting the preoperative regurgitant orifice boundary and identifying the residual shunt after surgery, confirming the value of this technology in interventional procedures for various cardiac diseases (Tamborini et al, 2021). In our study, this advanced 3D cardiac ultrasound technology was systematically applied to the preoperative and postoperative real-time imaging evaluation of LAAO in patients with various forms of LAA, to observe whether the morphology and position of the occluder are normal and to qualify, locate, and quantify any residual leakages around the occluder, providing a basis for individualized treatment planning after surgery.…”
Section: Discussionmentioning
confidence: 93%
“…In comparation, the photo-realistic techniques with a higher resolution allows for more realistic images of cardiac structures, by superimposing a virtual light source, which can be moved around and through the aneurysm, making realistic light and shadow effects to highlight the target structures, augmenting our understanding of the anatomical morphology. Studies have shown that novel 3DE rendering techniques can better delineate borders, orifices, cavities, and other structural abnormalities compared with 2DE and traditional 3DE, increasing the diagnostic confidence of readers and improving communication between the surgeon and the imaging specialist ( 4 , 14 , 15 ). To the best of our knowledge, this is the first case diagnosed with BCNIE with aortic valve involvement, leading to aortic valve perforation, and prolapse and development into a giant aortic root pseudoaneurysm using a series of novel three-dimensional echocardiographic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent enhancements in three-dimensional echocardiography (3DE) have been further improved as a result of novel transducers, software, and trans-illumination techniques, which provide plentiful and previously unavailable diagnostic information. Meanwhile, the TrueVue technique allows for novel photorealistic images of cardiac structures with a freely movable virtual light source integrated into the data set, effectively enhancing the depth perception and augmenting the visualization of anatomical structures ( 4 ). In addition, the TrueVue technology can be modified into a transparent mode, named TrueVue Glass, focusing on the blood pool–tissue interface; however, the tissue itself remains transparent, which leads to highlighted borders of the chambers, valves, and vessels within the heart ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transparency or “glass” effect allows the operator to adjust tissue transparency, thus improving the delineation of cardiac and extracardiac structures ( 34 ). This tool showed an incremental value compared to TI and standard 3D technology in the recognition of MV anatomy, border delineation, and pathogenetic mechanisms ( 35 ) ( Figures 3 , 4 ).…”
Section: Clinical Applications Of 3d Echocardiography In the Study Of...mentioning
confidence: 99%
“…Recently, new 3D rendering tools (TI and “transparency” effect) furtherly improve the visualization and delineation of MV anatomy and pathology, and improve localization of regurgitant jets compared with standard 3D rendering ( 32 , 34 ). 3D TEE imaging during procedures might be improved by TI and the “transparency” effect providing a better evaluation of leaflet grasping and of residual MR jets ( 35 ) ( Figure 7 ).…”
Section: Percutaneous Treatment Of Mitral Valve Prolapsementioning
confidence: 99%